DESIGN OF HIGH GAIN ULTRA WIDE-BAND ANTENNA FOR WIRELESS COMMUNICATION USING EBG STRUCTURES - Kaabal, A.; Ahyoud, S.; Asselman, A.; Faize, A. (European Scientific Journal, ESJ, 2013)
The properties of materials electromagnetic band-gap (EBG) and their advantage are being studied; then a high gain ultra-wideband (UWB) microstrip antenna using electromagnetic band-gap (EBG) structures concepts has been specifically designed in this paper. The -10 dB impedance bandwidth of the proposed antenna is 2.9–11.7 GHz about 251% broader, which is one of the most usable bandwidth regions for wireless applications such as WiMAX, WiFi outdoor, WLAN, Hiperlan and so on. The proposed antenna has an average gain of 6.6 dB and the peak is 18.99 dB at 4.19 GHz. The designing and simulation results done by using ANSOFT High Frequency Structure Simulator (HFSS), show that the antenna has higher gain than conventional UWB microstrip antenna.